2018
DOI: 10.3390/cancers10050142
|View full text |Cite
|
Sign up to set email alerts
|

A New Strategy to Control and Eradicate “Undruggable” Oncogenic K-RAS-Driven Pancreatic Cancer: Molecular Insights and Core Principles Learned from Developmental and Evolutionary Biology

Abstract: Oncogenic K-RAS mutations are found in virtually all pancreatic cancers, making K-RAS one of the most targeted oncoproteins for drug development in cancer therapies. Despite intense research efforts over the past three decades, oncogenic K-RAS has remained largely “undruggable”. Rather than targeting an upstream component of the RAS signaling pathway (i.e., EGFR/HER2) and/or the midstream effector kinases (i.e., RAF/MEK/ERK/PI3K/mTOR), we propose an alternative strategy to control oncogenic K-RAS signal by tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 181 publications
(342 reference statements)
0
22
0
Order By: Relevance
“…Our phylogenetic analysis showed that each of these cysteine residues (C104Y, C73Y, and/or C76Y) corresponded to an invariable cysteine that is responsible for zinc-coordination in the RING domain of SINA E3 ligase. Our results indicated the critical cysteine residues are required for proper SINA function in relaying RAS signal in Drosophila eye development (Figure 1) [31,32]. A majority of 28 newly isolated sina mutant alleles are embryonic lethal, resembling that of a large sina deletion allele, sina DF(81K72) [33].…”
Section: Three New Sina Ems Point Mutations In the Ring Domain Exhibimentioning
confidence: 76%
See 4 more Smart Citations
“…Our phylogenetic analysis showed that each of these cysteine residues (C104Y, C73Y, and/or C76Y) corresponded to an invariable cysteine that is responsible for zinc-coordination in the RING domain of SINA E3 ligase. Our results indicated the critical cysteine residues are required for proper SINA function in relaying RAS signal in Drosophila eye development (Figure 1) [31,32]. A majority of 28 newly isolated sina mutant alleles are embryonic lethal, resembling that of a large sina deletion allele, sina DF(81K72) [33].…”
Section: Three New Sina Ems Point Mutations In the Ring Domain Exhibimentioning
confidence: 76%
“…Thus, a large collection of 28 newly identified Our sequencing data revealed point mutations resulting in C104Y, C73Y, or C76Y substitutions in sina ES10 , sina ES79 , or sina ES473 , respectively, and a 10 base pair deletion in sina ES26 (Figure 1A and Table 1). The three C to Y amino acid substitutions mutated the invariable cysteine (Cys) amino acids that are responsible for zinc coordination in the RING domain of SINA [31,32] ( Figure 1A). Without proper SINA function, activation of upstream RAS/RAF/MAPK signals (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations